Unravelling the Impact of Fundamental Analysis on Stock Prices: A Study of Banking Companies Listed on the Indonesia Stock Exchange, 2017-2021 - Dewi Yulianty, Puspa; Mugayat, Ali; Nur’aeni, Anggun (Fakultas Pendidikan Ekonomi dan Bisnis, 2023)
This study aims to examine the influence of Debt to Equity Ratio (DER), Price Earning Ratio (PER), and Return On Equity (ROE) on stock prices of banking companies listed on the Bursa Efek Indonesia during the period 2017-2021. The population consists of 6 banking companies consecutively listed on the Infobank15 index during the specified period, totalling 30 financial reports, which were selected using a purposive sampling technique. Secondary data was utilized for analysis. Multiple linear regression analysis was employed as the analytical method. The findings indicate that, partially, Debt to Equity Ratio (DER) has a significant negative influence on the stock prices of banking companies during the period 2017-2021. Price Earning Ratio (PER) has a significant positive influence on stock prices of banking companies during the period 2017-2021. Similarly, return on equity (ROE) has had a significant positive influence on the stock prices of banking companies during the period 2017-2021. Collectively, the Debt to Equity Ratio (DER), Price Earning Ratio (PER), and Return On Equity (ROE) have a significant positive influence on the stock prices of banking companies during the period 2017-2021.